River Basin Management - Under a Changing Climate 2023
DOI: 10.5772/intechopen.105954
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in River Basin Management

Abstract: River basin management can increase biodiversity conservation, land productivity, ecosystem restoration, rehabilitation, and land reclamation. River basin management cannot be handled by one institution alone but requires cooperation and coordination with various parties. Community involvement in river basin management has a strategic role and is carried out based on the principle of sustainability that combines a balance between productivity and conservation to achieve river basin management goals. Community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Based on Table 3, it can be concluded that the existing conditions in each building before rainwater harvesting was implemented produced different run-off discharges. These run-off discharges have great potential if used as an alternative source of raw water in buildings [12].…”
Section: Runoff Discharge Analysismentioning
confidence: 99%
“…Based on Table 3, it can be concluded that the existing conditions in each building before rainwater harvesting was implemented produced different run-off discharges. These run-off discharges have great potential if used as an alternative source of raw water in buildings [12].…”
Section: Runoff Discharge Analysismentioning
confidence: 99%